From Syariah to Berkah: The Tradition of Ṣiḥḥaḥ Akad Nikah at Jam’iyyah Rifa’iyah - Istifadah, Nur; Nurhadi, Agus (International Journal Ihya’ ’Ulum al-Din, 2025)
This article examines the ṣiḥḥaḥ of marriage, still practiced by the Rifa’iyah community. The implementation of ṣiḥḥaḥ begins with negotiations between families and religious leaders, the selection of guardians, and the appointment of marriage witnesses. In addition, the bride-to-be learns the sciences of marriage, the improvement of two sentences of shahada. This research uses an ethnographic approach, focusing on the Jema’ah and Kyai Rifa’iyah. Data were collected in the field through observations, interviews with relevant parties, including the kyai (Rifa’iyah religious leader) and congregations, and documentation. Data analysis is an interactive process, namely data reduction, data display, and data verification. The research shows that the practice of ṣiḥḥaḥ until now is one of the efforts to preserve Tradition in the Rifa’iyah congregation, and its meaning has undergone a shift - from syari’ah – the ratification of the previous marriage akad – to berkah – hoping for blessings from the kyai, especially Rifa’iyah.